PERANCANGAN BUKU POP-UP ALFABET UNTUK ANAK BERKEBUTUHAN KHUSUS TUNA GRAHITA RINGAN GUNA MENINGKATKAN KEMAMPUAN VISUAL ANAK. - Ramadhan, Naufal Zaim; Riyanto, Darwin Yuwono; Fahminnansih, Fenty (Jurnal Art Nouveau, 2018)
The lack of understanding the society to children with special needs verbally and physically makes people do not know how to behave and communicate with them. Mentally Disabled is one of the children with special needs due to the condition of the child has far below the average of intelligence, which is characterized by the limitations of intelligence and inadequacy in social interaction. Based on the case, researchers want to design the learning Media that contains about the kind of alphabet. This research uses qualitative method by observation, interview, documentation and literature study to get data for designing the Media. This Media is a useful Pop Up Book as a medium of learning and media to introduce some stories to children with Mentally Disabled.